Cytologic features and staining characteristics of Gamna–Gandy bodies from seven canine fine-needle aspirate preparations. (November 2017) - Moore, A Russell; Leavell, Sarah E.; Conrado, Francisco O.; Beatty, Sarah S. K.; MacNeill, Amy L.
Gamna–Gandy (GG) bodies are non-infectious, hyphal-like structures associated with siderotic nodules in lymphoid tissue; GG bodies are very rarely reported in veterinary cytologic samples. Cytologically, GG bodies can be misidentified as hyphae or plant material. Seven canine lymphoid tissue aspiration cases that contained GG bodies were investigated for morphologic variability and staining characteristics. Available archived cytology slides containing GG bodies were stained with reagents known to show positive results (Prussian blue, Alizarin red S, Von Kossa) and negative results (Gomori methenamine silver) in histologic samples. Calcofluor white staining was also performed. GG bodies in Wright–Giemsa-stained cytology samples displayed considerable variability but were generally 2–5 µm diameter, 10–35 µm long, refractile, clear, pale-tan or pale-yellow, wavy or straight, tubular structures. Six cases allowed for cytochemical staining; staining properties were similar to histology samples. The bodies did not stain with calcofluor white; this stain may be helpful in distinguishing GG bodes from fungal hyphae.